2022
DOI: 10.3390/en15145097
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Linear Regression Model Based on the Most Influential Predictors for a Research Office Cooling Load

Abstract: Energy consumption in the building sector is a major concern, particularly in this time of worldwide population and energy demand increases. To reduce energy consumption due to HVAC systems in the building sector, different models based on measured data have been developed to estimate the cooling load. The purpose of this work is to develop a linear regression model for cooling load of a research room based on the radiant time series (RTS) components of the cooling load that consider the building material and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Fig. 1 LR Flow chart [17] Random Forest: Assume you have a forest with several trees, each with its own unique method of forecasting things.…”
Section: B Machine Learningmentioning
confidence: 99%
“…Fig. 1 LR Flow chart [17] Random Forest: Assume you have a forest with several trees, each with its own unique method of forecasting things.…”
Section: B Machine Learningmentioning
confidence: 99%
“…The results showed that the model performed well in predicting occupancy and showed satisfactory results. Similarly, in the article in [ 124 ], the authors described the development of a linear multi-regression model to predict the cooling load of a room in the Renewable Energy Research Laboratory at Mangosuthu University of Technology, using radiant time series method components. The model considered several predictors, including male and female occupants, window cooling load, and roof cooling load, which were identified as the most influential factors in determining the cooling load of the room.…”
Section: Data Analysis Approachmentioning
confidence: 99%
“…SWHs (FPC, ETC) sustainability life cycle environment in regions with low solar irradiation, such as the United Kingdom, was developed by simulation. The main conclusion was that solar thermal systems do not represent a more environmentally sustainable alternative to fossil fuel-based water heating (Mutombo & Numbi, 2022). Dust effect on the performance of the solar collector was analyzed in Hakizabera, Li, Yang, and Heli (2018).…”
Section: International Journal Of Sustainable Energy and Environmenta...mentioning
confidence: 99%